The Analyzing Materiality Level Consideration Based on Auditor’s Professionalism, Professional Ethics and Auditor’s Experience - Dwi Puryati; Nabila Prananda; Novelia Ellena Nur Fatimah (Jurnal Kajian Akuntansi, 2022)
AbstractThe objective of this study was to analyze the impact of an auditor's expertise, professional ethics, and experience on the level of materiality at a Public Accounting Firm in Bandung. This study methodology incorporated descriptive analysis and verification techniques. The research population consists of all auditors employed by a Bandung public accounting firm. The research sample was determined using a purposive sampling technique and the result was 41 auditors from 12 Public Accountant Firms in Bandung. Data collection techniques were carried out through questionnaires. The data analysis was carried out using regression analysis, determination coefficient, and hypothesis test. Before analyzing the data, instrument tests and classical assumption tests were carried out. The findings revealed a favorable and statistically significant effect of the auditor's professionalism, professional ethics, and experience on the amount of materiality considered by Bandung Public Accounting Firms. Consideration of the level of materiality was influenced by the auditor’s professionalism, professional ethics, and experience by 52.1%, while the other 47.9% was determined by other factors that were not researched in this study.Keywords: Auditor; Experience; Materiality; Professionalism; Professional ethics. AbstrakPenelitian ini dilakukan di Kantor Akuntan Publik di Kota Bandung dengan tujuan menganalisis pengaruh profesionalisme auditor, etika profesi dan pengalaman auditor terhadap pertimbangan tingkat materialitas. Analisis deskriptif dan verifikatif digunakan sebagai pendekatan dalam penelitian ini. Populasi penelitian adalah semua auditor yang bekerja pada Kantor Akuntan Publik di Kota Bandung. Sampel penelitian berjumlah 41 auditor dari 12 Kantor Akuntan Publik di Kota Bandung. Teknik penentuan sampel yang digunakan adalah purposive sampling. Pengumpulan data dilakukan melalui kuesioner. Metode analisis datayang digunakan adalah analisis regresi berganda, koefesien determinasi dan uji hipotesis. Sebelum data dianalisis dilakukan uji instrument dan uji asumsi klasik. Hasil penelitian menunjukkan pengaruh yang positif dan signifikan dari variabel profesionalisme auditor, etika profesi, dan pengalaman auditor terhadap pertimbangan tingkat materialitas. Profesionalisme auditor, etika profesi dan pengalaman auditor mempengaruhi pertimbangan tingkat materialitas sebesar 52.1%, sedangkan pengaruh dari faktor lain yang tidak diteiliti dalam penelitian ini sebesar 47.9%.Kata kunci: Auditor; Etika profesi; Materialitas; Pengalaman; Profesionalisme.